The 25 years of the Italian magazine "La Famiglia" - Cattaneo, Mario (Medicina e Morale, 1993)
In this article the Author first covers the steps that led to the creation, 25 years ago, and the the development of the magazine "La Famiglia", edited by "La Scuola" of Brescia (ltaly). This editorial iniziative was carried out in order to give a strong answer to the educational needs of the family, thus providing a truly interdisciplinary discussion about these problems. The magazine is in Iine with the christian and catholic prospective of the family.